Corruption Potential Of Environmental Funds In Overcoming Climate Change In Indonesia - Daryanti Daryanti; Raineven Sailano Violand Charnade (Faculty of Law, Universitas Lampung, 2022)
Indonesia's solemnity in dealing with climate change is demonstrated by ratifying the Paris Agreement 2015 treaty into Law of the Republic of Indonesia Number 16 of 2016 concerning the ratification of the Paris Agreement to the United Nations Framework Convention on Climate Change, which contains efforts to address climate change with the REDD+ program. The Government of Indonesia receives funding from REDD+, which addresses climate change in Indonesia. However, this creates the potential for corruption in using REDD+ funds by state officials. This study aims to understand the potential for corruption of environmental funds by government officials in reducing greenhouse gas emissions and anticipating climate change in Indonesia. This paper uses research method consisting of a qualitative research methodology with literature review research. The data analysis uses an objective case approach and a normative juridical approach. Based on several cases of misuse of environmental funds in Indonesia, it is not certain that the optimization to address climate change at the Ministry of Environment will work as it should to achieve the target as promised in Indonesia's NDC for 2030.